Dynamic characteristics of compound textured journal bearing. (July 2021) - Meng, Fanming; Zhang, Yifei; Su, Linlin; Yu, Haiyang; Zheng, Yong
An investigation of the compound texture effect on the dynamic characteristics of the journal bearing film is conducted. In this work, eight dynamic coefficients of the compound textured journal bearing and critical speed of the rotor supported by textured bearings are obtained and compared. Meanwhile, the elastic deformation effect of the bearing and rotor is obtained using the continuous convolution fast Fourier transform (CC-FFT) method. It is found that the reasonably arranged compound texture brings out an obvious increment in the direct stiffness coefficients and damping coefficients compared with the simple one, which results in the high critical speed of the bearing-rotor system. The above changes are close to the texture distribution, second-layered texture length, and width-length ratios of the compound texture. Moreover, there exists a critical compound texture depth to improve the critical speed of the bearing-rotor system.